Benzene Purity Improvement and Feed Amount Reduction on Benzene Production - Owena, Devina Neala Arva; Loeharja, Bruce Wills Steadman; Hardani, Halilintar; Cahyaningrum, Herda (Journal of Chemical Engineering Research Progress, 2024)
Global demand for benzene is expected to rise significantly. Previous research focused on extracting toluene from water, but a proposed shift towards preventive measures includes recycling toluene to avoid pollution and enhance benzene production. Emphasis on addressing separation ratios and material balance is crucial for successful simulations. Proposed innovations involve added splitters and shortcut columns for enhanced purity. Benzene production could be gained through the process of hydrodealkylation with some modifications. It shows the significant difference of the purity of benzene produced with the use of splitter and shortcut column compared to not using splitter and shortcut column. The recycling process effects the mass flow of the compound which picture the capability of a process to scale up. Through recycling the toluene, it also happens to cut or push the sum of the feed which leads the process to be more economical. Based on the modification of the benzene production it is resulted that the mass flow rate of the benzene production is significantly increased from 38.6 kg/h to 430.72 kg/h which gives possibility of the production to be higher in one go. Recycling toluene and hydrogen will also help the effectivity and efficiency of the process by its quality and specifically its quantity of the fresh feed. The modification also affects the purities of the benzene from 70.72% to 99.95%. Therefore, by doing the modification it will produce greater number of benzene with its high purities. Copyright © 2024 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).